Selenylated Imidazo[1,2-a]pyridine Induces Cell Senescence and Oxidative Stress in Chronic Myeloid Leukemia Cells - Burkner, Gabriella Teles; Dias, Dhébora Albuquerque; Souza, Kamylla Fernanda Souza de; Araújo, Anna Júlia Papa de; Basilio, Denise Caroline Luiz Soares; Jacobsen, Fernanda Tondello; Moraes, Ana Carolina Rabello de; Silva-Filho, Saulo Euclides; Cavalcante, Marcos Filipe de Oliveira; Moraes, Cassio Augusto de Oliveira; Saba, Sumbal; Macedo, Maria Lígia Rodrigues; et al. (Molecules (Basel, Switzerland), 2023)
Imidazo[1,2-a]pyridines (IPs) have been studied regarding drug development. The objective of this work was to evaluate the antileukemic capacity of IP derivatives by screening their ability as a pro-oxidant. IP derivatives were synthesized and oral bioavailability and toxicity were analyzed in silico. Redox screening was performed on human Kasumi, KG-1, K562, and Jurkat leukemia cells. The IP derivative and the most responsive leukemic cell were selected for cytotoxicity, cell proliferation, cell senescence, and oxidative stress assays. The predictive toxicity analysis showed a possible effect on the reproductive system, but without mutagenic, carcinogenic, or irritability effects. MRK-107 against K562 cells was the compound that showed the best redox profile. MRK-107 did not induce cell death in K562 and monocyte cells. However, this compound was able to decrease cell proliferation and increase cell senescence after 48 and 72 h. Furthermore, MRK-107 induced oxidative stress in K562 cells after 72 h, increasing lipid peroxidation and decreasing reduced glutathione (GSH) contents. This study demonstrated that MRK-107-induced senescence with the involvement of oxidative stress is a possible mechanism of action, addressing this compound as a potential antitumor drug against chronic myeloid leukemia.